Use of social online media to improve life skills in online media literacy of children and youth - Wattanathum, Chatchayapha (International Journal of Psychosocial Rehabilitation, 2020)
The purposes of this research were to create, develop and investigate of online social media for enhance life skill: media literacy of children and youth. The samples used in the research were voluntary and volunteered to participate in activities, with parental consent and support. There were 30 children and youth aged between 9-16 years old. The research area consisted of 5 communities in the Khlong Lat Prao area, including Chao Por Somboon 54 community, Roi-Krong community, Bang Bua Ruam Chai community (Saphan Mai 2), Run Mai Pattana community and the Ruam Mit Rang Satta community. The research tools used for data collection were 1) Focus Group interview form, 2) Expert quality evaluation form for online storytelling books and online media literacy (Content) which is an assessment of the 5 level assessment scale, 3) The evaluation form for the quality of experts towards the electronic story book online combined with the subject of media literacy (technical) is an evaluation form of the 5 level assessment scale, 4) The expert opinion form for the knowledge test Media literacy (IOC), and 5) Activity schedule for learning about media literacy by using the training for 3 days, in a total of 24 hours. 6) Online story books and electronic storytelling combined with media literacy.